EVOLUTION OF INEQUALITY IN LATIN AMERICA (1980-2014): A MULTIDIMENSIONAL APPROACH BEYOND INCOME - Carmen Trueba; Lorena Remuzgo (Revista de Economía Mundial, 2017)
Latin America is the region with the greatest inequality in terms of incomes. Thus, during the last years, the United Nations Development Programme (UNDP) has showed concern about the obstacle that inequality causes in the human development of this region. Given that higher economic growth does not necessarily lead to the achievement of further progress social, development beyond income will be one of the most important UNDP’s messages for its upcoming report for this region to be launched early 2016. In this paper, we propose a new multidimensional approach to study inequality in welfare in terms of the components of the Human Development Index of the UNDP –health, education and income– in the period 1980-2014. For this purpose we use the multidimensional inequality indices proposed by Maasoumi (1986) that can be decomposable into the between- and within-group inequality components.